2015
DOI: 10.1515/biol-2015-0029
|View full text |Cite
|
Sign up to set email alerts
|

Ileal transposition in rats influenced glucose metabolism and HSP70 levels

Abstract: Objective: Ileal transposition procedure (IT), in combination with sleeve gastrectomy, is widely used to induce diabetes remission and to control related metabolic abnormalities. A transposition of a long segment of distal ileum in obese Zucker rats improved glucose tolerance 6 months after IT. The premise of our study was to to examine the long - term effects of ileum transposition on the liver glycolytic enzymes content in a euglycemic group of operated Zucker rats. Methods: Twenty male Zucker rats underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…The obtained results suggest that the combination of DJOS and a change of the diet was a strong stimulus for HSP70 level induction in plasma and liver tissue. In our previous study, we reported increased HSP70 plasma levels after the ileal transposition (IT) in comparison to SHAM-operated, diabetic fatty Zucker rats (Stygar et al 2015 ). Angelini and co-workers showed that duodenal-jejunal bypass surgery leads to a decrease in levels of plasma HSP70 in obese, insulin-resistant (IR) and nonalcoholic fatty liver disease (NAFLD) subjects (Angelini et al 2018 ).…”
Section: Discussionmentioning
confidence: 96%
“…The obtained results suggest that the combination of DJOS and a change of the diet was a strong stimulus for HSP70 level induction in plasma and liver tissue. In our previous study, we reported increased HSP70 plasma levels after the ileal transposition (IT) in comparison to SHAM-operated, diabetic fatty Zucker rats (Stygar et al 2015 ). Angelini and co-workers showed that duodenal-jejunal bypass surgery leads to a decrease in levels of plasma HSP70 in obese, insulin-resistant (IR) and nonalcoholic fatty liver disease (NAFLD) subjects (Angelini et al 2018 ).…”
Section: Discussionmentioning
confidence: 96%
“…and Stygar et al . 43 , 59 . Briefly, 2% isoflurane with 2 l/min oxygen flow under spontaneous breathing was used to induce and maintain anaesthesia; analgesia was performed with xylazine (5 mg/kg b.w., ip; Xylapan, Vetoquinol Biovet, Poland) and antibiotic prophylaxis with gentamicin (5 mg/kg b.w., im, KRKA, Poland).…”
Section: Methodsmentioning
confidence: 99%
“…For RYGBP, the gastric bypass model was established following a previously described protocol (23). For IT surgery, Treitz's ligament was identified, the jejunum was divided 5 cm aborally and the ileal loop was the interpositioned in an isoperistaltic fashion, forming two end-to-end anastomoses (24). For the combination of RYGBP and IT surgery, Treitz's ligament was identified, the jejunum was divided 5 cm aborally and anastomoses were formed in the distal jejunum and proximal.…”
Section: Animalsmentioning
confidence: 99%